Intraoperative stereotactic magnetic resonance imaging for deep brain stimulation electrode planning in patients with movement disorders - Jakobs, Martin; Kloss, Manja; Neumann, Jan-Oliver; Campos, Benito; Unterberg, Andreas; Kiening, Karl (World neurosurgery, 2018)
Objective - Implantation of deep brain stimulation (DBS) electrodes requires stereotactic imaging. Stereotactic magnetic resonance imaging (MRI) for DBS surgery has become more popular and intraoperative MRI scanners have become more available. We report on our cohort of movement disorder patients who underwent intraoperative stereotactic MRI-only DBS electrode implantation. - Methods - A review of our DBS database for eligible patients over a study period of 8 years was performed. Stereotactic accuracy was calculated as a directional error and the Euclidean distance between planned and controlled electrode positions. Number and choice of microelectrodes, procedural times and complications were documented. - Results - n = 86 surgeries in n = 81 patients with Parkinson's Disease (PD), essential tremor and dystonia were performed and n=167 electrodes were implanted. Mean Euclidean distance between planned and controlled target was 2.1mm (±0.6). The directional error showed that electrodes were implanted more medial (0.3mm ± 0.9), posterior (0.5mm ± 1.0) and inferior (0.6mm ±1.0) compared to plan. There were no significant differences for stereotactic accuracy between targets, hemispheres or order of implantation. No significant correlations between Euclidean distance and number of microelectrode tracts or volume of intracranial air were observed. N = 539 microelectrodes were applied. In 28.7% non-center trajectories were chosen. Length of tremor (−61 minutes) and PD (−121 minutes) surgeries could be reduced significantly over the course of the study period. N = 1 (1.2%) intracranial hemorrhage occurred. N = 1 (0.6%) electrode had to be repositioned for lack of clinical effect. - Conclusion - Intraoperative stereotactic MRI for DBS surgery is feasible with high stereotactic accuracy and low rates of complication.
Gesehen am 26.02.2020